Elements of argumentation - Besnard, Philippe, 1958- (MIT Press, 2008)
Here the authors introduce techniques for formalizing deductive argumentation in artificial intelligence, emphasising emerging formalizations for practical argumentation. They discuss how arguments can be constructed, how key intrinsic and extrinsic factors can be identified, and how these analyses can be harnessed in the real world.